Comportamiento agronómico de la soya (Glycine max (l) con dos biofertilizantes orgánicos en la época de verano en el cantón Quvedo. - Tovar Tovar, Diana Narcisa (2016)
This paper describes the study of the efficiency of bio-fertilizers, based on bovine manure + legume + ash + rice husk and cattle manure + + lime molasses in the agronomic performance of the soybean (Glycine max (L.) Merril ) in the summer in the canton Quevedo. Biofertilizantes organic foliar application on soybean crop INIAP 308 at 10, 20 and 35 days after planting conducted at doses of 300, 150, L / ha-1. The following objectives, evaluate the agronomic performance of soybean cultivation INIAP-308 with two organic bio-fertilizer application at different doses in the Quevedo, determine the best organic biofertilizers in crop yield soybean INIAP-308, set the best dose per hectare of organic biofertilizers in the production of soybean cultivation INIAP-308, in which the design of complete randomized block (DBCA) on a 2x3 factorial arrangement with four replications was used. Days to flowering, loading height, plant height, number of seeds per pod, grain moisture dl, 100 seed weight, yield per hectare. The results show that the biofertilizers has an effect on the agronomic performance for their nutritional content to be assimilated contains soy, treatment T2 (bovine manure + legume + ash + rice husk + 300 L / ha-1) He presented the best results in the variables height of 16.00 cm load, number of seeds per pod with 3.00 semillas199.20 weight of 1000 g, yield to 4129.99 kg / ha-1